Migraine Is More Than Just Headache: Is the Link to Chronic Fatigue and Mood Disorders Simply Due to Shared Biological Systems? - Karsan, Nazia; Goadsby, Peter J. (Frontiers in Human Neuroscience, 2021)
Migraine is a symptomatically heterogeneous condition, of which headache is just one manifestation. Migraine is a condition of altered sensory thresholding, with hypersensitivity amongst sufferers to sensory input. Advances in functional neuroimaging have highlighted that several brain areas are involved prior to pain onset. Clinically, patients can experience symptoms hours to days prior to migraine pain, which can warn of impending headache. These symptoms can include mood and cognitive change, fatigue and neck discomfort. Some epidemiological studies have suggested that migraine is associated in a bidirectional fashion with other disorders, such as mood disorders and chronic fatigue, as well as with other chronic pain conditions such as fibromyalgia. This review will focus on the literature surrounding alterations in fatigue, mood and cognition in particular, in association with migraine, and the suggested links to disorders like chronic fatigue syndrome and depression. We hypothesise that migraine should be considered a neural disorder of brain function, in which alterations in aminergic networks integrating the limbic system with the sensory and homeostatic systems occur early and persist after headache resolution and perhaps interictally. The associations with these other disorders may allude to the inherent sensory sensitivity of the migraine brain, and shared neurobiology and neurotransmitter systems.